Environmental, social, and governance (ESG) and corporate governance in ASEAN: a threshold effects of corporate strategy - Siti Nur Aqilah Ab Wahab; Nik Hadiyan Nik Azman; Zamri Ahmad (Universiti Malaysia Sarawak, 2024)
Sustainable development goals (SDGs) constitute 17 sets of goals to be achieved by the end of the said year. The SDGs prioritize problems associated with hunger, inequality, climate change, environmental destruction, peace, and justice for a better global future (United Nations, 2018). This study has two objectives, first, to examine the relationship between corporate governance mechanisms and corporate sustainability performance across ASEAN-listed companies. Second, to explore the threshold effect of corporate strategy in a nexus relationship between corporate governance mechanisms and corporate sustainability performance. This study uses 118 companies in ASEAN-5 countries as study’s sample. The period covers from 2011-2020. Both fixed effect model and fixed effect threshold regression are employed to capture linear and nonlinear estimation, respectively. The study validates the female directors and the independent directors on ASEAN boards positively impacts corporate sustainability. Intriguingly, the intervention of corporate strategy will mitigate the low company’s ESG score while strengthening the link between corporate governance and ESG score. This study has practical implications for companies, investors, and regulators looking to in incorporate ESG factors into capital expenditure decisions and reporting..